(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article discusses the degree of influence of the U.S. in strengthening the independence of the countries of Central Asia. On this basis reveals the ultimate purpose of the United States in the Central Asian region, which lies in the geopolitical dominance in the context of the implementation of the national interests of Washington. Key words: foreign policy of the United States, the New Independent States, the national interest, geo-political dominance.